Innovations in the international financial markets - Gerhard Maier (Intereconomics, 1986)
The appearance of the international financial markets is changing rapidly; new instruments are constantly being hatched and marketed, often with considerable success. However, the ingenuity of the markets does not always meet with applause; the banking supervisory authorities and central banks view the rapid pace of innovation with concern and the banking community also displays occasional unease. On balance, do the positive aspects outweigh the negative ones?
Keywords: 330; Banking